On the empirical relevance of the exchange rate as a shock absorber at the zero lower bound - David Finck; Mathias Hoffmann; Patrick Hürtgen (Deutsche Bundesbank, 2023)
We estimate the effects of a negative asymmetric demand shock on the real exchange rate for the euro area vis-à-vis the United States, Canada, and Japan by state-dependent sign-restricted local projection methods. We find a real depreciation when interest rates are not at the ZLB, but also when they are. The exchange rate can accomodate considerable variations in output, confirming its shock-absorbing capacity before and during the ZLB episode. The stabilizing role of the exchange rate is accompanied by a significant expansion of the ECB's balance sheet at the ZLB, while it remained unaffected in the pre-ZLB period. Our empirical results can be reconciled with an open economy New Keynesian model extended with unconventional monetary policy measures when interest rates are at the ZLB.
Keywords: F31; E31; E37; C54; 330; Zero Lower Bound; Exchange Rate; Local Projections; State-dependent Effects; Unconventional Monetary Policy; Demand Shocks